Islamic Legal Politics in Indonesia: The Dynamics of Sharia Integration in the National Legal System - Sofwan Tambunan; Zaini Munawir; Ahmad Senang (Jurnal Sahabat ISNU SU, 2025)
This study examines the politics of Islamic law in Indonesia and the dynamics of sharia integration within the national legal system. As a Muslim-majority country, Indonesia faces challenges in balancing the aspirations of Muslims with the principles of a pluralistic rule of law. The objectives of this study are to analyze the development of Islamic law from the colonial period to the modern era, to understand the process of integrating Islamic law through formal regulations, and to evaluate the challenges and prospects for the development of Islamic law within the context of national legal politics. The research method used is normative legal research with a statutory, historical, and conceptual approach. Data were obtained through a literature review of laws and regulations, academic literature, historical documents, and previous research on Islamic law and legal politics in Indonesia. The analysis was conducted qualitatively to interpret the relevance of sharia norms, national regulations, and the dynamics of legal politics. The results show that Islamic law in Indonesia developed through a long process of adaptation, starting from limited recognition during the colonial period, through the strengthening of religious courts and marriage law at the beginning of independence, to the integration of sharia economics in the modern era. State legal politics plays a strategic role in determining the direction of legislation, balancing the interests of the Muslim majority with the constitution, and ensuring the effective functioning of Islamic law. Key challenges include social diversity, regulatory harmonization, and implementation capacity. However, development prospects remain open through a maqasid al-Shariah-based approach. In conclusion, the integration of Islamic law in Indonesia is not merely a formality, but part of a national legal framework that is adaptive, relevant, and grounded in justice and the public interest. It is recommended to strengthen the capacity of religious courts, harmonize regulations, and raise public legal literacy to ensure Islamic law plays an optimal role in the national legal system.